Histologic and morphologic character of pediatric renal artery occlusive disease - Coleman, Dawn M; Heider, Amer; Gordon, David; Ganesh, Santhi K; Eliason, Jonathan L; Stanley, James C (Journal of vascular surgery, 2021)
The pathologic nature of pediatric renal artery occlusive lesions causing renovascular hypertension has been the subject of numerous anecdotal reports. This study was undertaken to define the character of childhood renal artery stenoses. A better understanding of this disease is particularly germane, given its unknown etiology and the limited success of certain contemporary treatment options. Renal artery specimens obtained during open operations in children being treated for renovascular hypertension from 2004 to 2016 were studied. Excluded from study were arteries subjected to earlier open or endovascular operations. Histologic preparations employing hematoxylin-eosin, Movat, Masson trichrome, and Verhoeff-van Gieson stains allowed characterization of the intima, media, and adventitial tissues. External and luminal diameters were measured. Microscopic data were correlated with preoperative arteriographic images. The histologic and morphologic findings were assessed in regard to coexistent nonrenal arterial and aortic lesions as well as known syndromic diseases. Thirty-three stenotic renal arteries from 28 children were subjected to examination. Stenoses involved the proximal-ostial renal arteries (24), central renal arteries (7), and distal segmental renal arteries (2). Ostial stenoses commonly exhibited preocclusive concentric hyperplasia of intimal tissues, frequent internal elastic lamina disruptions, and diminutive and discontinuous media. Central and distal renal stenoses most often exhibited lesser intimal cellular hyperplasia and more noticeable fibrodysplasia of the media and adventitia. The mean external and luminal diameters of the renal arteries having ostial stenoses were smaller than the expected renal artery size for a given age. Abdominal aortic coarctation or hypoplastic aortas occurred in 14 children. Neurofibromatosis type 1 affected four children with ostial renal artery disease and one child with midrenal artery disease, but there were no distinguishing features unique to their stenoses. Pediatric renal artery stenotic disease affects exceedingly small arteries. Ostial lesions frequently exhibit extensive luminal encroachments characterized by cellular hyperplasia of intimal tissues and scant medial smooth muscle. Central and distal renal arterial stenoses were characterized most often by extensive fibrodysplasia of the media and adventitia. The early success and durability of catheter-based angioplasty may be compromised by the cellular abnormalities of pediatric renal artery occlusive disease observed in this investigation.